Absence of significant association between UGT2B4 genetic variants and the susceptibility to anti‐tuberculosis drug‐induced liver injury in a Western Chinese population. (14th March 2020) - Chen, Hao; Jiao, Lin; Zhou, Juan; Bai, Hao; Lyu, Mengyuan; Wu, Tao; Wu, Lijuan; Song, Jiajia; Liu, Tangyuheng; Yan, Hong; Ying, Binwu
Abstract: What is known and objective: Combination regimens of six‐month duration may increase the incidence of anti‐tuberculosis drug‐induced liver injury (ATLI), which is clinically characterized by mild cholestasis and hepatocanalicular lesions. UGT2B4 is a predominant UDP‐glucuronosyltransferase enzyme in the human liver that plays an important role in the detoxification of bile acids, which yields water‐soluble inactive compounds that can easily be excreted in the bile or urine. This study aimed to investigate the potential association between UGT2B4 variants and the susceptibility to ATLI. Methods: Genomic DNA was extracted from whole blood sample of each patient, and all SNPs were genotyped using an improved multiplex ligation detection reaction method. Clinical symptoms and laboratory results were recorded regularly. Five genetic variants at UGT2B4 (rs1131878, rs1966151, rs28361541, rs4557343 and rs79407331) were identified in a prospective study of 118 ATLI cases and 628 non‐ATLI controls. All participants were treated by first‐line anti‐TB drugs in Western China Hospital. The potential association between SNPs, ATLI risk and clinical phenotypes were determined based on the distribution of allelic frequencies and different genetic models. Results and discussion: Statistical comparisons of cases and controls after correction for multiple testing did not yield any significant association between genetic variants at UGT2B4 and risk of ATLI via the analyses of single locus and subgroup differences. What is new and conclusion: This is the first study aimed to investigate the association of UGT2B4 polymorphisms with ATLI risk. Our results revealed that UGT2B4 genetic variants are unlikely to confer susceptibility to ATLI in the Western Chinese Han population. Abstract : The predominant UDP‐glucuronosyltransferase enzyme, UGT2B4, is a key regulator of bile acid biosynthesis and is involved in liver metabolism. This is the first study that investigated the association of UGT2B4 polymorphisms with anti‐tuberculosis drug‐induced liver injury in a Western Chinese population.